Design of the energy-saving technology of assembling connections with the interference - Зенкін, А. С.; Оборський, І. Л. (Eastern-European Journal of Enterprise Technologies, 2012)
In the work the examined questions of methodology and procedure of selection with the aid of the developed program set with the design of the technology of the technological parameters of assembling the connections with the interference, assembled by thermal methods, taking into account energy-econom